Reporting and design elements of audit and feedback interventions: a secondary review. Issue 1 (25th January 2016) - Colquhoun, Heather; Michie, Susan; Sales, Anne; Ivers, Noah; Grimshaw, J M; Carroll, Kelly; Chalifoux, Mathieu; Eva, Kevin; Brehaut, Jamie
Abstract : Background: Audit and feedback (A&F) is a frequently used intervention aiming to support implementation of research evidence into clinical practice with positive, yet variable, effects. Our understanding of effective A&F has been limited by poor reporting and intervention heterogeneity. Our objective was to describe the extent of these issues. Methods: Using a secondary review of A&F interventions and a consensus-based process to identify modifiable A&F elements, we examined intervention descriptions in 140 trials of A&F to quantify reporting limitations and describe the interventions. Results: We identified 17 modifiable A&F intervention elements; 14 were examined to quantify reporting limitations and all 17 were used to describe the interventions. Clear reporting of the elements ranged from 56% to 97% with a median of 89%. There was considerable variation in A&F interventions with 51% for individual providers only, 92% targeting behaviour change and 79% targeting processes of care, 64% performed by the provider group and 81% reporting aggregate patient data. Conclusions: Our process identified 17 A&F design elements, demonstrated gaps in reporting and helped understand the degree of variation in A&F interventions.